2006
DOI: 10.1149/1.2354453
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Adhesion of Electrodeposited Copper on Anodized Thin-Film Aluminum for LIGA Microfabrication

Abstract: The nucleation and electrodeposition of copper from a pyrophosphate electrolyte onto anodized thin-film aluminum was used to provide well-adhering electroforms in high aspect-ratio resist molds made by X-ray lithography. Cyclic voltammetry and chronoamperometry methods were employed to characterize the impact of process variables on initiating copper deposition onto an anodized aluminum film. Adhesion of the electroplated films was evaluated using a 90°peel test. Several aluminum films were studied to elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Above m/z Ͼ 100, peaks at m/z 104, 105, 106, 108, and 110, as well as m/z = 116, 117, 118, 119, 120, 122, and 124 were identified corresponding to Pd + and Sn + , respectively, according to the standard isotope peaks and corresponding abundances of the isotope database. 21 Secondary ion peaks were observed at m/z = 121, 123, and 125, which have been assigned to 106 PdNH + , 108 PdNH + , and 110 PdNH + , respectively. No Sn + related peaks are expected at this location.…”
Section: Resultsmentioning
confidence: 98%
“…Above m/z Ͼ 100, peaks at m/z 104, 105, 106, 108, and 110, as well as m/z = 116, 117, 118, 119, 120, 122, and 124 were identified corresponding to Pd + and Sn + , respectively, according to the standard isotope peaks and corresponding abundances of the isotope database. 21 Secondary ion peaks were observed at m/z = 121, 123, and 125, which have been assigned to 106 PdNH + , 108 PdNH + , and 110 PdNH + , respectively. No Sn + related peaks are expected at this location.…”
Section: Resultsmentioning
confidence: 98%
“…[39][40][41][42] The third class summarizes techniques following the method of thermal spraying. [43][44][45] In the fourth class, chemical plating, contains electroless [46][47][48][49] and electrochemical plating. [50][51][52][53] Each of the above-mentioned methods has certain advantages and disadvantages for the formation of Al-Cu joints.…”
mentioning
confidence: 99%
“…It was reported that the Cu nucleation density on the barrier layer decreases as the overpotential decreases [11]. When the Cu nucleation density was low, the adhesion of the Cu plated on the Ti surface as a barrier layer could be poor [12]. Therefore, the electroplated Cu on the Ti surface was partially delaminated and wrinkled, as shown in Fig.…”
Section: Effects Of the P-ratio And Current Densitymentioning
confidence: 98%